Synthetic trap-peptides identify a TOM complex phosphatase: PP2A dephosphorylates Tom6 - Scheinost, Laura; Ludwig, Christina; Höfflin, Nico; Taskin, Asli Aras; Marada, Adinarayana; Vögtle, Friederike-Nora; Meisinger, Christof; Köhn, Maja (The FEBS journal, 2026)
The identification of phosphatases that dephosphorylate specific sites in proteins remains a major challenge, particularly for the major class of serine/threonine-specific phosphatases, which function as holoenzymes. Here, we report the development of synthetic trap-peptides to identify phosphatases that bind to Tom6, a subunit of the mitochondrial translocase of the outer membrane (TOM) complex. The TOM complex is regulated by reversible phosphorylation, and although responsible kinases have been identified, the corresponding phosphatases so far remain unknown. Here, the trap-peptides enriched phosphoserine/threonine-specific protein phosphatases 2A (PP2A) and 4 (PP4) as full holoenzymes from yeast cytosolic fractions. We observed that their interaction with Tom6 was mediated through their regulatory subunits Cdc55reg and Psy2reg, respectively, and that PP2A was able to dephosphorylate Ser16 of Tom6 in vitro. In summary, synthetic trap-peptides facilitate the identification of complete holoenzymes that bind to the target sequence and reveal PP2A as the first TOM phosphatase.
Online veröffentlich am 02. September 2025
Gesehen am 19.02.2026